Foot Plantar Pressure Measurement Using Low Cost Force Sensitive Resistor (FSR): Feasibility Study: Foot Plantar Pressure Measurement - Jor, A.; Das, S.; Bappy, A. S.; Rahman, A. (Journal of Scientific Research, 2019)
Plantar pressure measurement is an essential and effective strategy in the assessment of foot musculoskeletal safety and footwear comfort. It is commonly applied in clinical gait analysis, sports and foot biomechanical studies. But most of the devices used for plantar pressure measurement are high cost and not readily available for the research. This study aims to present a low cost foot plantar pressure measurement system based on force sensitive resistor (FSR). The system is composed of low cost electronic instrumentation through FSR, arduino, LCD display, baseboard and a power bank. To verify the feasibility and effectiveness of the system, a linear load vs. pressure calibration test was made and a group of female participants performed static trials on heels of three different heights. Experimental results and comparative analysis showed that this system has stable performance in static measurements of plantar pressure.